Dairy microbiology a practical approach - Papademas, Photis (Boca Raton, FL : Taylor and Francis, 2015)
The objective of this book is to provide a scientific background to dairy microbiology by re-examining the basic concepts of general food microbiology and the microbiology of raw milk while offering a practical approach to the following aspects: well-known and newfound pathogens that are of major concern to the dairy industry. Topics addressed include Cronobactersakazakii and its importance to infant formula milk or Mycobacterium avium subspecies paratuberculosis (MAP) that might be connected to chronic human diseases (Crohn's), the role of dairy starter cultures in manufacturing fermented dai.
Front Cover Dedication Preface Contents Chapter 1: Basic Concepts of Food Microbiology Chapter 2: The Microbiology of Raw Milk Chapter 3: Dairy Pathogens: Characteristics and Impact Chapter 4: Dairy Starter Cultures Chapter 5: Application of Probiotics in the Dairy Industry: The Long Way from Traditional to Novel Functional Foods Chapter 6: Application of Molecular Methods for Microbial Identifi cation in Dairy Products Chapter 7: Application of Food Safety Management Systems (FSMS) in the Dairy Industry Color Plate Section Back Cover.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Dairy microbiology; Food -- Safety measures; Probiotics; SCIENCE -- Life Sciences -- Biology; SCIENCE -- Life Sciences -- Microbiology; Dairy microbiology; Food -- Safety measures; Probiotics; Electronic books